2022
DOI: 10.1002/anie.202117316
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Unprecedented Route to a Library of Thermostable Formaldehyde‐Derived Polyesters: Highly Active and Selective Copolymerization of Cyclic Acetals and Anhydrides

Abstract: The development of new strategies for producing polyesters can expand the category of biodegradable materials. Here, we disclose the alternating copolymerization of cyclic acetals (made from formaldehyde and diols) and anhydrides for the first time, using 5 cyclic acetals and 9 anhydrides to afford 45 unprecedented polyesters. At a wide range of reaction temperatures (25 to 140 °C), diverse metal-free Lewis/Brønsted acids are highly active catalysts for these copolymerizations via the cationic mechanism. Of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Cationic ring-opening copolymerizations between different types of cyclic monomers, such as cyclic ethers, cyclic esters, and cyclic acetals, exert great potential, particularly in controlling monomer sequences, tuning the physical properties of polymers, providing copolymers with degradability, and overcoming inertness, such as nonhomopolymerizability. The features attained by copolymerization rather than homopolymerization are ascribed to various possible reactions, such as propagation, backbiting, and transacetalization reactions, that occur during cationic ring-opening polymerization. In addition, two main types of propagation mechanisms may occur in cationic ring-opening polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic ring-opening copolymerizations between different types of cyclic monomers, such as cyclic ethers, cyclic esters, and cyclic acetals, exert great potential, particularly in controlling monomer sequences, tuning the physical properties of polymers, providing copolymers with degradability, and overcoming inertness, such as nonhomopolymerizability. The features attained by copolymerization rather than homopolymerization are ascribed to various possible reactions, such as propagation, backbiting, and transacetalization reactions, that occur during cationic ring-opening polymerization. In addition, two main types of propagation mechanisms may occur in cationic ring-opening polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanisms for chain initiation, chain propagation, and structural evolution were elusive. The ceiling temperature for THF homopolymerization was about 83 °C, , and the homopolymerization of THF is thermodynamically forbidden at 120 °C. However, the ABB-type units with two continuous THF were still formed at such high reaction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As a 4-carbon building block, THF can increase the ester linkage separation in alternating polyesters, thus accelerating hydrolysis and polymer degradation . However, THF and other heterocycles with low ring strain energy does not copolymerize with cyclic anhydrides via the anionic mechanism. It has been shown that a tri­(isobutyl)­Al­(III)/water catalyst system could mediate the anhydrides (A)/epoxides (B)/THF (C) terpolymerization to produce poly­(ester- alt -ether) containing ABC sequences in excess THF . Very recently, Kerr and Williams found that a phenoxy-imine Zr­(IV) also yielded a copolymer comprising a ring-opened phthalic anhydride (PA) (A), the following epoxide (or oxetane) (B), and a THF (C) from oxygenated heterocycles (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of sequence-controlled polymers, which offers new pathways to a variety of physical, mechanical, and chemical properties in myriad applications, is challenging . Among sequence-controlled polymers, alternating copolymers are generally prepared using comonomer pairs, such as olefins and cyclic anhydrides, , olefins and CO, aziridines and CO, , aziridines and carbonyl sulfide, , cyclic acetals and cyclic anhydrides, epoxides and CO 2 , epoxides and CO, and epoxides and cyclic anhydrides. However, in most cases, sequence skipping prevents the formation of perfectly alternating copolymers. , Additionally, the scope of comonomer pairs is limited; for example, only a few examples of the alternating copolymerization of epoxides and lactones have been reported, which yield low-molecular-weight polymers. Coates and co-workers reported the alternating copolymerization of dihydrocoumarin with epoxides to form alternating polyesters with molecular weights of 7–19 kDa .…”
mentioning
confidence: 99%